Study of Morphological Features of Sea Buckthorn Leaves by Luminescent and Stereomicroscopy Methods - N. A. Kovaleva; O. V. Trineeva; A. A. Gudkova; A. I. Slivkin (Разработка и регистрация лекарственных средств)
Introduction. Sea buckthorn – Hippophaё rhamnoides is a perennial shrub, the fruits of which are a source of carotenoids and are harvested on an industrial scale to obtain a number of drugs. Recently, not only fruits, but also other parts of the plant, such as buds, leaves, shoots and bark, are of increasing interest. It is known that sea buckthorn leaves are rich in compounds such as tannins, polyunsaturated fatty acids and vitamins (C and E). The rich composition of biologically active substances with a sufficient content of components allows us to consider leaves as a new type of medicinal plant material for the further development of various preparations based on them. In addition, the leaves are an annually renewable raw material and it is possible to harvest them on an industrial scale, since this valuable medicinal plant is cultivated everywhere in Russia. Data on the microscopic characteristics of the fruits of sea buckthorn are described in detail in the scientific literature, which cannot be said about the leaves. The scientific literature also does not describe the features of the luminescence of the tissues of the leaves of the sea buckthorn.Aim. The aim of this work was to study the possibility of using the luminescent and stereomicroscopic methods of analysis to determine the main morphological features of the leaves of the sea buckthorn.Materials and methods. Dried whole leaves of a plant of the genus Hippophaës collected in the Voronezh region were used as the object of the study. The study of microdiagnostic signs was carried out according to the State Pharmacopoeia of the XIV RF GPA.1.5.3.0003.15 «Technique of microscopic and microchemical examination of medicinal plants and herbal medicinal products». A stereomicroscopic study was carried out using a Biomed 2 microscope. The luminescence of the tissues of the sea buckthorn leaves was investigated using a luminescent microscope of the Miсromed 3 LUM brand.Results and discussion. Stereomicroscopic analysis of sea buckthorn leaves was carried out. High-resolution volumetric images were obtained in a short period of time. It was found that the characteristic microscopic features of the leaves are the presence of a large number of corymbose hairs along the upper and corymbose-stellate along the lower surfaces, including the vein and petiole (from colorless to white, yellow and dark brown). Single simple stellate hairs are rare. When removing the layer of hairs, the spongy structure of the epidermis of the leaf is visible. The carried out luminescent analysis made it possible to reveal the features of the luminescence of the tissues of the leaves of the sea buckthorn. Diagnostic luminescent features include: the most pronounced yellow glow is observed for the cells of the base of the corymbose hair; the plates that make up the corymbose hairs do not have bright fluorescence; stellate hairs do not have a glow; pronounced yellow-green fluorescence is characteristic of the leaf vein.Conclusion. For the first time, stereomicroscopic and luminescent analyzes of sea buckthorn leaves were carried out and the main morphological features of this type of medicinal plant material and their biometric characteristics were established. The carried out luminescent analysis made it possible to reveal the features of the luminescence of the tissues of the leaves of the sea buckthorn.